Medida de centralidade por intermediação em teoria dos grafos na caracterização e análise da malha viária urbana da sede do município de Santarém/Pa - REIS, Gabriela Cacilda Godinho dos (Universidade Federal do Oeste do Pará, 2024)
By means of geoprocessing techniques, georeferenced data of the urban road network of the municipality of Santarém, state of Pará, can be converted into a graph, where the vertices are the intersections and the edges are the paths between them. The use of the statistical computing environment R, through the igraph library, makes it possible to reach the betweenness centrality of a vertex or edge. This measure of centrality is related to the structural importance that a node or edge has inside a network. To find the most important paths in relation to betweenness centrality it is necessary to count the number of times each vertex or edge is traversed by a minimum path. The betweenness centrality is indicative of influence, of greater or lesser traffic allowed, consequence on the others, in case of removal, alteration or interruption. Considering the unorganized urban expansion, together with the increasing use of motor vehicles, poor urban planning and the difficulty of adapting the infrastructure of the roads to the growing demand, which have generated congestion and difficult mobility in urban roads, this work is proposed, which aims to use the betweenness centrality in graph theory to verify which are the most important routes for displacement of the urban road network of the municipality of Santarém, state of Pará.